Reflection of Yakutia History in Siberian Lights Journal in 1920—1980 - E. I. Krasilnikova (Научный диалог)
The article traces the dynamics of representations of the historical past of Yakutia in the publications of the monthly literary, artistic and socio-political magazine “Siberian Lights”. This issue is considered in the context of the processes of constructing the Soviet policy of memory throughout the entire period of the existence of the USSR. The relevance of the study is due to the increased attention to the specifics of historical knowledge presented in the public space, to its structures, interpretations and use for political and ideological purposes in the past and present. The novelty of the study is seen in the fact that until now the history of journal representations of the past of Yakutia in the context of state policy has not become the subject of independent scientific research. The study made it possible to identify the contexts that determined the specifics of creating journal representations of the history of Yakutia. The author established and characterized five stages of this representation. It is shown how the meanings and techniques of the politics of memory that were behind the approaches to the description and characteristics of the past of Yakutia changed. It is proved that the differences between approaches to representations were determined by the tendencies of strengthening and weakening the political and ideological control of the state in the field of memory politics and nation building.